The Local Fisher Community Learning Center in Accordance with the Sufficiency Economy Philosophy of Ban Pak Don Sak, Surat Thani Province, Thailand - Phongphanich, Nara (Rajapark Journal, 2022)
This academic article was to describe the process of studying and developing the local fisher community learning center in accordance with the Sufficiency Economy Philosophy of Ban Pak Don Sak, Surat Thani Province, Thailand. The aims of this work were to study and survey cultural capital and to transfer knowledge by establishing a learning center for local fishing communities based on the Sufficiency Economy Philosophy. This work was done through a process of participation from all sectors known as the “working group”, consisting of 5 faculty members from Surat Thani Rajabhat University, 30 community leaders and representatives, 5 people from Don Sak District, and 5 people from Donsak Municipality. Data collection was done using a documentary research, observation, local history, and in-depth interviews. Data analysis used content analysis method, using the collected data to systematize the data, and the working group together to synthesize and explain the phenomenon that has occurred. The results revealed that the cultural capital of the Ban Pak Don Sak community was the Phetchaburi people, who settled in 1933 with unique characteristics in art, culture, local wisdom, and the way of life of the people also known as “Khon Mueang Nai.” In addition, community leaders and representatives were also found to gain knowledge and increase their skills in “communicator”, “community-based tourism”, “promoting community potential according to the philosophy of sufficiency economy” and “establishing a learning center”; and leads to brainstorming, manpower, mobilization of local fishing materials or tools for establishing a concrete of the local fisher community learning center.